Acid Mine Drainage Water For Alternative Electrical Energy Sources - Aurora Sari Dharma Yanti; Mahtuf Ikhsan (Fakultas Sains dan Teknologi UIN Sunan Kalijaga, 2016)
Acid Mine Drainage (AMD) refers to the outflow of acidic water from metal mines or coal mines. AMD has high acidity, which has potency for conductor. The aim of this research was to demonstrate the ability of acid mine water as an alternative conductor of electrical energy. The research revealed that 500 ml AMD could supply 1,5 watt lamp for 30 days.